Cost-effectiveness of Oral Protease Inhibitors Co-administration versus Pegylated Interferon-Α2b and Ribavirin Only for the Patients with Hepatitis C Genotype 1 in Kazakhstan Health Care Settings - Alima ALMADIYEVA; Serik IBRAYEV; Assiya TURGAMBAYEVA; Alexandr KOSTYUK; Zayituna KHISMETOVA; Zhanar AKHMETOVA (Tehran University of Medical Sciences, 2018)
Background: The triple therapy including peginterferon, ribavirin and protease inhibitors was more effective compared to the combination of only peginterferon and ribavirin. This study aimed to assess the cost-effectiveness of triple treatment in either treatment-naïve and treatment-experienced patients in Kazakhstan. Methods: A Markov model was created to assess long-term clinical advantages and the cost-effectiveness of the triple therapy from Kazakhstan payer perspective. Health state transition probabilities, pharmaceutical and other costs (according to the price in 2015), and utility rate were acquired from the published studies and publicly available sources. All used costs and benefits were discounted at 5% per year. Results: Despite treatment background, the patients, receiving boceprevir and telaprevir, were estimated to experience less serious liver-disease complications, more life-years, and more QALYs compared to the patients having standard of care. For treatment-experienced group, boceprevir and telaprevir were dominant, with more QALYs. For all the groups of patients, incremental costs per QALY gained were between USD14995 and USD18075. The total average cost of boceprevir is slightly more costly than a standard duration of treatment with telaprevir, and so is the average cost per SVR. Extensive sensitivity analyses verified robust model results. Conclusion: The inclusion of protease inhibitors to standard management for the therapy of patients with genotype 1 chronic HCV infection in Kazakhstan is predicted to be cost-effective using a typically applied willingness to pay threshold of USD37805 (3 times GDP per capita).